Do Institutions and Technologies Matter for Trade Openness? Empirical Evidence from African Countries. Issue 5 (3rd September 2021) - Nguyen, Canh Phuc; Doytch, Nadia; Dinh Thanh, Su; Schinckus, Christophe
ABSTRACT: This study examines the influence of institutions, the Internet, and mobile phone usage on African countries' trade openness. Applying various estimations for a balanced panel of data for 47 African economies over the period of 2003 to 2017, our empirical analysis arrives at the following interesting conclusions. Improvement of the institutional framework has mixed impacts on the trade relationships of African countries within the continent. Notably, internet and mobile phone usage have greater impacts on trade openness in countries that have a better institutional framework.